Correction: Validation of a novel direct-injection chemiluminescence-based method for N-nitrosamine analysis in advanced-treated recycled water, drinking water, and wastewater. Issue 3 (17th February 2022) - Roback, Shannon L.; Kodamatani, Hitoshi; Fujioka, Takahiro; Plumlee, Megan H.
Abstract : Correction for 'Validation of a novel direct-injection chemiluminescence-based method for N -nitrosamine analysis in advanced-treated recycled water, drinking water, and wastewater' by Shannon L. Roback et al., Environ. Sci.: Water Res. Technol., 2020, 6, 1106–1115, DOI: ; 10.1039/C9EW00943D .